Prevention of Sexual Grooming in Adolescent Gadget Users through Kalyanamitta - Adhiviyanto, Dirga Yuka Okta; Setyawan, Purwoko Ariya; Silasari, Silasari; Suyatno, Tri; Sukarti, Sukarti (LPPM STIAB JINARAKKHITA LAMPUNG, 2024)
Misuse of this technology is often used for fraud, pornography and other violence, Sexual Grooming is one form, where the victims targeted by perpetrators are teenagers especially those who use social media. Perpetrators use social media to approach victims by establishing relationships until the victim wants to perform sexual acts. This study was conducted to explain the occurrence of Sexual Grooming in adolescents through gadget media, explain the role of kalyanamitta in the prevention of Sexual Grooming in adolescents, and explain the study of Sutta Pitaka related to efforts to prevent Sexual Grooming in adolescents using gadgets through strengthening Kalyanamitta. The method used is a descriptive method which is a type of research that provides an overview or description of all circumstances as clearly as possible without any treatment of the object under study. Based on this research, Kalyanamitta helps in the prevention of Sexual Grooming with efforts to develop Hiri-Ottapa, Sati-Sampajanna to the emergence of panna as a savior.